The Tax Cuts and Jobs Act : An Appraisal - Chalk, Nigel (IMF Working Papers; Working Paper, 2018)
This paper assesses the landmark Tax Cuts and Jobs Act (TCJA), from the perspective of both the U.S. itself and the wider world. The reform has many positive aspects including steps to broaden the base of, and reduce marginal rates under, the personal income tax (PIT), reduce distortions to investment and financing decisions, and mitigate outward profit shifting. But the TCJA has a large fiscal price tag and leaves significant uncertainty as to how the U.S. tax system will develop. The PIT changes could have better targeted relief at low earners, and there is scope to more fully address distortions in business taxation. The novel international provisions create a complex array of both positive and negative international spillovers, and have the potential to significantly reshape the wider international tax system.